Procedures performed by general dental practitioners, dental hygienists and prophylaxis assistants in oral healthcare practices in the Netherlands - Joost CL den Boer; Wil JM van der Sanden; Katarina Jerković-Ćosić; Josef JM Bruers (BMC Oral Health)
Abstract Background Within Dutch oral healthcare practices, collaboration between general dental practitioners, dental hygienists and prophylaxis assistants is common practice. However, little is known about the precise procedures that the various professional groups involved carry out. The aim of this study was to map this collaboration through an analysis of the division of tasks, as shown in treatment records. Materials and methods For the purpose of this study, a Dutch corporate dental company provided retrospective data on all procedures conducted in 32 affiliated practices in 2022. Separate datasets were created to analyse the data at the procedure, patient, care provider and practice level. The Chi-square test, the independent-samples T-test, and One-way ANOVA were employed. All analyses were performed using SPSS and an alpha level of 0.05 was used. Results A general practitioner was involved in the treatment of 94.6% of the patients. All procedures except initial periodontal treatment were performed by at least 75% of the general dental practitioners. 80.5% of the dental hygienists performed initial periodontal treatment. Over 90% of the prophylaxis assistants performed procedures for oral hygiene education and calculus removal. Significant differences were observed between practices, particularly in preventive procedures. Conclusions In general, the general dental practitioner performs a broad range of procedures, at least in the practices that are affiliated with the corporate dental company of this study. Dental hygienists proved to be an important executor in the field of periodontal treatments. The care provided by the prophylaxis assistant focused mainly on prevention. However, significant differences in the division of tasks were observed, even within this group of practices within one corporate dental company.